Activity and Regulation of Various Forms of CwlJ, SleB, and YpeB Proteins in Degrading Cortex Peptidoglycan of Spores of Bacillus Species In Vitro and during Spore Germination - Li, Yunfeng (American Society for Microbiology, 2013)
Germination of Bacillus spores requires degradation of a modified layer of peptidoglycan (PG) termed the spore cortex by two redundant cortex-lytic enzymes (CLEs), CwlJ and SleB, plus SleB's partner protein, YpeB. In this study, in vitro and in vivo analyses have been used to clarify the roles of individual SleB and YpeB domains in PG degradation. Purified mature Bacillus cereus SleB without its signal sequence (SleB(M)) and the SleB C-terminal catalytic domain (SleB(C)) efficiently triggered germination of decoated Bacillus megaterium and Bacillus subtilis spores lacking endogenous CLEs; previously, SleB's N-terminal domain (SleB(N)) was shown to bind PG but have no enzymatic activity. YpeB lacking its putative membrane anchoring sequence (YpeB(M)) or its N- and C-terminal domains (YpeB(N) and YpeB(C)) alone did not exhibit degradative activity, but YpeB(N) inhibited SleB(M) and SleB(C) activity in vitro. The severe germination defect of B. subtilis cwlJ sleB or cwlJ sleB ypeB spores was complemented by ectopic expression of full-length sleB [sleB(FL)] and ypeB [ypeB(FL)], but normal levels of SleB(FL) in spores required normal spore levels of YpeB(FL) and vice versa. sleB(FL) or ypeB(FL) alone, sleB(FL) plus ypeB(C) or ypeB(N), and sleB(C) or sleB(N) plus ypeB(FL) did not complement the cortex degradation defect in cwlJ sleB ypeB spores. In addition, ectopic expression of sleB(FL) or cwlJ(FL) with a Glu-to-Gln mutation in a predicted active-site residue failed to restore the germination of cwlJ sleB spores, supporting the role of this invariant glutamate as the key catalytic residue in SleB and CwlJ.